PERNAFASAN PURSED LIP BREATHING MENINGKATKAN SATURASI OKSIGEN PENDERITA PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DERAJAT II - Amira Permata Sari Tarigan; Juliandi Juliandi (Jurnal Online Keperawatan Indonesia, 2018)
Chronic Obstructive Pulmonary Disease (COPD) is one of the main causes of morbidity and mortality throughout the world. According to WHO, COPD is currently the fifth cause of death worldwide. COPD sufferers need action in the form of pulmonary rehabilitation which aims to control, reduce symptoms and increase functional capacity optimally so that patients can live independently and be useful to the community. The purpose of this study was to look at the effect of breath pursed lip breathing exercises on oxygen saturation of patients with second degree COPD. This type of research is pre experimental design, with one group pre test - post test design. Polpulasi in this study were all patients with grade II COPD in H. Adam Malik Hospital Medan with a total sample of 36 people. The average oxygen saturation before anf after pursed lip breathing exercise were 96,72 % and 98,11 %. The results of this study indicated that there was an influence of pursed lip breathing exercise on oxygen saturation of patients with second degree COPD (P value=0.001, Î±=0,05) It was recommended that health workers in charge of COPD Police at Adam Adam Malik Hospital have the ability and time to train COPD patients in pursed lip breathing exercises to maintain oxygen saturation in COPD patients within normal limits.